Inovasi Kemasan untuk Meningkatkan Daya Tarik Produk Risole Mayo G2J dalam Pasar UMKM - Atikah, Nabilah Nur; Hidayah, Nischa Purnama; Utami, Lili; Hasanah, Uswatun (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Packaging innovation is an important strategy in increasing product attractiveness, especially in the Micro, Small and Medium Enterprises (MSME) market. This research focuses on the Risole Mayo G2J product, which is a popular snack food. Through a creative and functional packaging design approach, this research aims to explore how attractive packaging can influence consumer perceptions and increase sales. The methods used include consumer surveys and packaging design analysis. The research results show that innovative packaging not only attracts consumers' attention but also provides significant added value to the product. Thus, packaging innovation can be the key to increasing the competitiveness of MSME products in an increasingly competitive market.